KAJIAN SOSIOLOGIS TRADISl PATI KA ATA MATA DALAM MASYARAKAT SUKU LIO DI DESA, FLORES, NUSA TENGGARA TIMUR - Mbere, Theresia Sindianti; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
This study focuses on the sociological study of the Pati ka ata mata Rite in the Lio Tribe Comtmunity in Paga Village, Flores, East Nusa Tenggara. The purpose of his study is to describe and examine the sociological study of the pati ka ata mata rite in the Lio tribe. This research is a qualitative approach with descriptive-explanative type. The theory used as a scalpel in reviewing this research is Emile Durkehin's Traditional Religion Theory. The results of this study reveal that the Pati ka ata mata. ritua contains the principles of implementing the pati ka ata mata ritus, the purpose of the implementation of the pati ka ata mata Rite, sociological Dimensions of the Pati ka ata mata Rite, As a cultural rite, pati ka ata mata contains a sociological dimension. Keywords: culture, pati ka kata mata, traditional, sociological